Rosacea fulminans with rhinophyma and severe eye complications in a young woman treated with isotretinoin - Pogorzelska-Dyrbuś, Joanna; Sosnowski, Marek; Szepietowski, Jacek (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2021)
Rosacea is an inflammatory skin disease that affects the cheeks, nose, chin and forehead [1]. Rosacea fulminans is an extremely rare variant of rosacea, previously called pyoderma faciale, which usually occurs in healthy young women. It is characterised by an abrupt onset of erythematous papules, pustules, nodules and cysts on the background of – often severe – redness. The most worsened late stage of rosacea is called rhinophyma. The name, which was first used by Hebra in 1845, derives from the ancient Greek word “rhis”, which means nose, and “phyma”, meaning growth [2].